ANALISIS KONSUMSI KONSUMEN PADA SWALAYAN DAN MINIMARKET - Afrizal - (JURNAL AKADEMIKA)
This research seeks to develop a business strategy putting the groceries that are tailored to consumer consumption patterns in the Self. The next process is to categorize the items that are used as a reference layout improvements, so get recommendations for improvement layouts stating that sugar is approximated with bread, tea, coffee, and milk. Thus, the arrangement of merchandise can be adjusted with the association rules to fit the consumption patterns of consumers.